The expected performance of cloud optical and microphysical properties derived from Suomi NPP VIIRS day/night band lunar reflectance. Issue 23 (9th December 2013) - Walther, Andi; Heidinger, Andrew K.; Miller, Steven
Abstract [1] The day/night band channel of the Visible Infrared Imaging Radiometer Suite (VIIRS) instrument on board Suomi‐National Polar Partnership (S‐NPP) is a visible/near‐infrared sensor (500–900 nm band pass) capable of measuring extremely low magnitudes of light, down to the levels of reflected moonlight and beyond. Whereas similar measurement capabilities have existed on predecessor sensors (principally, the Defense Meteorological Satellite Program), the day/night band offers the first calibrated radiance measurements, and as a result, it is the first opportunity to apply moonlight measurements to the problem of retrieving nocturnal cloud optical properties. Daytime retrievals of cloud properties such as top height, optical thickness, cloud top particle size, and water content, have been conducted routinely from an assortment of operational and research grade optical sensors for decades. These observations are providing a satellite‐based global data record of increasing relevance to climate change monitoring (where clouds are thought to play an integral feedback role). The lack of a complete diurnal record of such key parameters presents an important shortfall of these records. Here we present the adaption of the daytime cloud optical and microphysical properties algorithm, which derives cloud optical thickness and effective radius from reflected sunlight to lunar reflectance. The new algorithm is referred to nighttime lunar cloud optical and microphysical properties. Day/night consistency of optical depth is shown through global analysis for one complete day of VIIRS data. Limitations of the retrieval of effective radius are discussed.